Design of Conceptual Framework for Measuring Operational Performance of Third-Party Logistics - Wahyu Andy Prastyabudi; Rizqa Amelia Zunaidi; Nabilla Adinna Cahyani; Hendrawan Widianto; Arda Erico Yuda; Elsa Diaz Yamila (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2020)
Abstract— The logistics business is expected to soar significantly, for which will reach 30 percent by 2020, driven by the growth of transaction of e-commerce. This growth, indeed, requires an apparent concern from the transporter logistics to continuously enhance their performance. On the other hand, the performance of logistics transporters will provide a positive contribution to the increase of LPI (Logistics Performance Index) score of Indonesia. Thus, the development of performance measurement systems is necessary to maintain the competitiveness level of logistic actors. This study provides a comprehensive overview of performance measurement systems in regard to the 3PL (third party logistics) companies. The goal of this study is to develop such a conceptual framework that portrays the essential elements necessary to take into account when implementing performance monitoring system to the 3PL companies. The conceptual framework is established using grounded-theory approach which comprises of four main steps: collecting and mapping data sources, categorizing the data, identifying and naming concepts, and establishing a conceptual model. The framework itself, is constructed into two main stages: 1) developing KPIs, 2) measuring the performance. To exhibit the applicability of the proposed approach, a numerical experiment is provided. This research has two main contributions. First, the study fills the theoretical gap pertaining to the concept of performance assessment systems in case of 3PL companies. Second, in practical view the proposed conceptual framework contributes to the academia by describing the basis of establishing performance monitoring as well as to the practitioners who wish to better measure performance in the transporter logistics.